Youth Sport Coaches’ Perspective on Positive Youth Development and its Worth in Mainstream Coach Education Courses - Santos, Fernando (2018)
Positive youth development (PYD) is a framework that has been widely used within sport research to outline sport’s potential as a developmental context. Past research has indicated how coaches play important roles in facilitating PYD through sport and yet, PYD-related material remains largely absent from mainstream coach